Influencia de los influencers en las decisiones de compra de consumidores, estudio de la publicidad nativa en plataformas digitales - Jurado Coloma, Nayely Johana (2025)
This project analyzed the influence of digital leaders in the purchase acquisitions of acquirers through the study of native advertising on digital platforms, using qualitative and quantitative methods, surveys and interviews with the audience and digital marketing experts were conducted to assess how the dissemination strategies employed by content creators impact the preferences and purchase behaviors. This study examined how digital promoters, through content designed to integrate naturally into platforms, contribute to the perception of trust and credibility of brands, which directly affects the purchase intention of users. The analysis begins with the evolution of native advertising, highlighting the characteristics, as well as the role of influencers in digital marketing. After this, a description was made detailing the techniques applied to manage data, deepening the relevance of user experiences and what were those strategies used by content creators. In addition, it was investigated how emotion connection and personalization influenced advertising acquisitions within different digital platforms. Finally, this study employed recommendations to leverage the use of digital leaders and native advertising, emphasizing the importance of establishing real contributions with digital promoters to maximize their impact of user consumption, this inquiry, provided recommendations to optimize the use of influencers and native advertising in purchasing decisions.